2020
DOI: 10.1002/chem.202000159
|View full text |Cite
|
Sign up to set email alerts
|

DMT1 Inhibitors Kill Cancer Stem Cells by Blocking Lysosomal Iron Translocation

Abstract: Cancer stem cells (CSC) constitute a cell subpopulation in solid tumors that is responsible for resistance to conventional chemotherapy, metastasis and cancer relapse. The natural product Salinomycin can selectively target this cell niche by directly interacting with lysosomal iron, taking advantage of upregulated iron homeostasis in CSC. Here, inhibitors of the divalent metal transporter 1 (DMT1) have been identified that selectively target CSC by blocking lysosomal iron translocation. This leads to lysosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…Furthermore, in Calu-1 lung cancer cells and HT-1080 fibrosarcoma cells, IRE-binding protein 2 (IREB2) is an essential gene for erastin-induced ferroptosis by regulating TFRC, FTH1 and FTL (1). Furthermore, several studies have suggested that inhibition of DMT1 may prevent iron translocation, leading to lysosomal iron overload, ROS production and ferroptotic cell death in cancer stem cells (35), and sulfasalazine induced ferroptosis is reduced by the inhibitory effect of estrogen receptor on TFRC and DMT1 in breast cancer cells (36). Artemisinin compounds sensitize cancer cells to ferroptosis by regulating IRP/IRE-controlled iron homeostasis (37).…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in Calu-1 lung cancer cells and HT-1080 fibrosarcoma cells, IRE-binding protein 2 (IREB2) is an essential gene for erastin-induced ferroptosis by regulating TFRC, FTH1 and FTL (1). Furthermore, several studies have suggested that inhibition of DMT1 may prevent iron translocation, leading to lysosomal iron overload, ROS production and ferroptotic cell death in cancer stem cells (35), and sulfasalazine induced ferroptosis is reduced by the inhibitory effect of estrogen receptor on TFRC and DMT1 in breast cancer cells (36). Artemisinin compounds sensitize cancer cells to ferroptosis by regulating IRP/IRE-controlled iron homeostasis (37).…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%
“…DMT1 is a widely expressed key iron transporter located within the plasma membrane and membranes of lysosomes and endosomes, which enables the uptake of Fe 2+ to the cytosol following iron endocytosis. DMT1 inhibitors were selected as a target in cancer stem cells by blocking lysosomal iron translocation, which leads to lysosomal iron accumulation, and thus production of ROS and induction of ferroptotic cell death (35). DMT1 is also involved in sulfasalazine-induced ferroptosis via activation of iron metabolism in breast cancer cells (36).…”
Section: Role Of Ncrnas In Ferroptosis and Cancer Developmentmentioning
confidence: 99%
“…Therefore, in this current review, we summarize the small-molecule compounds targeting the Wnt, Hh, Notch, and Hippo pathways to kill CSCs. Although targeting ferroptosis to kill CSCs has recently been invoked, the effects have been strongly established by many studies [143,147,148]. Recently, although biologics have been rapidly developed, smallmolecule compounds are still needed for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ironomycin can effectively reduce the number of CSCs in docetaxel-resistant xenograft models [143,147]. Furthermore, ebselen, substituting pyrazole, and benzyl isothiourea, which are the inhibitors of DMT1, can selectively target BCSCs by blocking iron in lysosomes [148]. These results indicate that increasing iron levels in lysosomes can initiate cell death in a manner similar to ferroptosis, and thus specifically and effectively kill CSCs.…”
Section: Ferroptosis and Small-molecule Compoundsmentioning
confidence: 91%
“…Further activities reported for pyrazolyl-pyrimidones and pyrazolyl-pyridines might similarly be the consequence of metal chelation rather than the attributed activity, including a recently reported activity of 3 and 5 against cancer cells. 38 Note that potentially metal chelating 2,2′-diazabiaryls such as pyrazolyl-pyrimidones are not listed in PAINS (pan-assay interference compounds). [39][40][41] Indeed a systematic checking of our compounds with the PAINS filter from RDkit does not flag any molecule in the series.…”
Section: Pyrazolyl-pyrimidones and Pyrazolyl-pyridines In Chemical Spacementioning
confidence: 99%